2018
DOI: 10.24926/iip.v9i4.1382
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacist’s Role in a Dental Clinic: Establishing a Collaborative and Interprofessional Education Site

Abstract: Background: Dental patients often have comorbidities and take multiple medications, some of which could impact their dental health and treatment.  A pharmacist in a dental clinic can assist with the gathering, documentation and evaluation of a dental patient’s medication history as it pertains to their dental visit and overall health.  Purpose: To develop and implement a collaborative and interprofessional education program with a pharmacist providing services in a dental school clinic.     Summary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The University of North Carolina (UNC) Adams School of Dentistry (ASOD) has sought to better address these barriers within its practice clinics through clinical partnerships with the UNC Eshelman School of Pharmacy (ESOP) to offer clinical pharmacy services as it has identified patients in North Carolina who come from 74 out of the 100 counties that are dental provider shortage areas, and 59 of these counties are primary care and behavioral health shortage areas as well [2]. Pharmacists contribute significantly to patient outcomes in health care environments and have also begun to explore models in dental practice [26][27][28][29][30][31].…”
Section: Chronic Diseases and Oral Healthmentioning
confidence: 99%
“…The University of North Carolina (UNC) Adams School of Dentistry (ASOD) has sought to better address these barriers within its practice clinics through clinical partnerships with the UNC Eshelman School of Pharmacy (ESOP) to offer clinical pharmacy services as it has identified patients in North Carolina who come from 74 out of the 100 counties that are dental provider shortage areas, and 59 of these counties are primary care and behavioral health shortage areas as well [2]. Pharmacists contribute significantly to patient outcomes in health care environments and have also begun to explore models in dental practice [26][27][28][29][30][31].…”
Section: Chronic Diseases and Oral Healthmentioning
confidence: 99%
“…Pharmacists collaborate with dentists in a variety of ways, many of which fall outside the traditional dispensing role of the pharmacist. A review of the literature has identified pharmacists in academic dental practice settings providing medication reconciliation services, antimicrobial stewardship, assisting in appropriate opioid prescribing, facilitating interprofessional education, didactic lecture, and smoking cessation counseling 1–13 . Choi et al.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…A review of the literature has identified pharmacists in academic dental practice settings providing medication reconciliation services, antimicrobial stewardship, assisting in appropriate opioid prescribing, facilitating interprofessional education, didactic lecture, and smoking cessation counseling. [1][2][3][4][5][6][7][8][9][10][11][12][13] Choi et al described pharmacists having a positive impact on improving the accuracy of patient medications in the dental record. 1 Gross described an antibiotic stewardship effort between dentists, pharmacists, and physicians in an academic dental practice that resulted in a decrease in antibiotic prescribing.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Overall, pharmacists were accepted by the dentistry team and patients with very few repercussions. 1 The purpose of this commentary is to propose a solution towards multiple issues identified by the author during her experience as an interprofessional pharmacist. We propose telehealth to be the solution to these issues.…”
mentioning
confidence: 99%
“…Overall, pharmacists were accepted by the dentistry team and patients with very few repercussions. 1 …”
mentioning
confidence: 99%